International Logistics Management - Aykor, A. Mert (Academician Publishing Book DOI Portal, 2023)
This book serves as a guide on international logistics management. The author, A. Mert Aykor, is an expert in the field of international logistics management and an academic. The book covers the principles, history, and evolution of international business logistics. Additionally, it examines global business logistics strategies, operations, and the art of leadership. The book will be a valuable resource for professionals, students, and researchers working in the field of logistics.